ABOUT THREE-DIMENSIONAL MODELS OF OSTEOSYNTHESIS SYSTEMS - Ilaria Loredana Petrovici; Mihai Catalin Tenovici; Razvan Cristian Vaduva; Danut Nicolae Tarnita; Georgiana Vintila; Dragos Laurentiu Popa (Journal of Industrial Design and Engineering Graphics, 2019)
Implantology is based on the failure of orthopedic treatment, or cases where orthopedic treatment is incapable of reducing or maintaining, for example, fracture of the femoral neck with movement. The advantage of centromedular fixation is that it allows the bone to physically load as much as possible, minimizing the risk of implant failure. The drawbacks of conventional nails have been eliminated with the introduction of the centromedular stem locking system. The purpose of this study was to obtain several virtual biomechanical systems on which to study several types of tibial fractures and several osteosynthesis systems. Starting from the tomographic images of the tibia, a virtual model of this bone component was developed. This model was "finalized" and modified using certain Geomagic techniques and then imported into SolidWorks. The osteosynthesis element used was the rigid classical nail with orthopedic screws which was modeled using the direct observation and measurement method. It is intended that these virtual components to be used to make orthopedic virtual osteosynthesis systems that are then analyzed in Ansys with the finite element method.